Effect of water pressure and axial static stress on evolution of impact energy and damage characteristics of red sandstone - Jiefang JIN; Yu WANG; Lixing FANG; Huiying XIONG; Youfeng XIAO; Xiaowang PENG (Meitan xuebao)
Deep underground project takes place in an environment characterised by high water pressure and geostress. This poses a significant risk of disasters such as water surges and destabilisation of the peripheral rock body, especially under dynamic disturbances such as blasting. It is of paramount importance to investigate the evolution of rock energy and the damage characteristics resulting from the joint action of water pressure and geostress, both in theory and in engineering practice. Impact tests were conducted on red sandstone specimens using a self-developed rock dynamics test system that employs high hydraulic pressure and high stress. The specimens were subjected to various hydraulic pressures and axial static stresses while maintaining the same impact load. The resulting dynamic stress-strain curves were analysed to determine the evolution of energy reflectance, energy transmittance and energy dissipation rate with respect to water pressure and axial static stress. Furthermore, the strain rate effect on the energy dissipation rate of the rock was characterised. The rocks after impact were screened and the longitudinal wave velocity was measured, its fractal dimension and damage variables were determined, and the effects of varying water pressure and axial static stress on the rock (mass)'s damage and crushing properties were investigated. The findings indicate that as water pressure increases, the amplitude of reflected waves decreases whilst that of transmitted waves increases. Furthermore, the stress-strain curves of rocks transform from type I to type II. In addition, the reflectance of energy from red sandstone decreases rapidly at first before changing gradually as water pressure increases. The transmittance of energy, on the other hand, increases exponentially as the water pressure increases, and the axial static stress impacts the correlation between the two. As water pressure gradually increases from zero, the rate of energy dissipation initially increases briefly before continuously decreasing. The correlation between the two variables follows a reliable Gaussian function. Axial static stress impacts the relationship between the rate of energy dissipation in rocks and water pressure. As the axial static stress increases, so does the rate of energy dissipation. Additionally, the trend of increasing energy dissipation rate follows an increase and then a decrease in water pressure. The red sandstone energy dissipation rate displays a clear strain rate effect, whereby an increase in strain rate results in an overall increase followed by a decrease in the red sandstone energy dissipation rate. As water pressure increases, the dynamic damage of red sandstone decreases gradually. Furthermore, the fractal dimension depicts a trend of "gradual decrease-transient increase-sharp decrease to zero". Water pressure increases transiently as the fractal dimension of breakage increases in response to an increase in the axial static stress.